Animal utilization based on local knowledge in Ciletuh Geopark, Ciemas Subdistrict, Sukabumi, West Java, Indonesia - INDRI WULANDARI; Sya Sya Shanida; TEGUH HUSODO; ERRI NOVIAR MEGANTARA; DEDE TRESNA (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Wulandari I, Shanida  SS, Husodo T, Megantara EN, Tresna D. 2019. Animal utilization based on local knowledge in Ciletuh Geopark, Ciemas Subdistrict, Sukabumi, West Java, Indonesia. Biodiversitas 20: 2781-2789. Ciletuh Geopark has high biodiversity but has not been supported by local knowledge about the use of animals to support sustainable development. This study aims to investigate: (i) the number of species that are used, (ii) distribution of local knowledge about animals using, and (iii) the dependency of communities on creatures in Ciletuh Geopark, Ciemas Subdistrict, Sukabumi. Mixed methods of qualitative (semi-structured interviews) and quantitative methods (proportional random sampling) were applied in this study. The community uses 153 species, consisting 58 Avifauna species, 13 mammals species, nine Herpetofauna species, three insects species, 16 species of freshwater fish, 43 species of seawater fish, two Mollusca species, and nine crustacean species. Utilization of fauna is not distributed in each village. Animals using of Avifauna, Herpetofauna, insects, and mammals tend to be utilized by people of Girimukti Village. Seawater fish, Mollusca, and crustaceans tend to be utilized by Ciwaru Village, while freshwater fish tend to be used in each village, except Girimukti and Cibenda Village. Utilization of fauna in Ciemas Subdistrict has begun to be abandoned, although several people still use them.